MEDICINAL BIOMAGNETISM FOR THE TREATMENT OF OBESITY : PRESENTATION OF THE 3D PROTOCOL - Vergínia Campagnollo Bueno, Ana; Gonçalves Seneda, Michelli; Mara Rambo, Ângela; Clara Campagnolo Gonçalves Toledo, Ana; Cabral de Azevedo, Caroline; Viapiana Bossa, Adriane (Health and Society, 2023)
Obesity is a chronic disease that affects a large part of the population and can develop several outcomes such as cardiovascular disease, type II diabetes and some types of cancer. As a result, it favors negative aspects both for the individual and for the public power. Faced with this problem, there is a need for new forms of treatment to improve the quality of life of these patients and reduce public spending. New alternatives to traditional medicine are needed for complementary non-drug treatments. Among them is Medicinal Biomagnetism (MB), a technique developed by Dr. Isaac Goiz Durán, which aims to promote body homeostasis using medium intensity magnets. It is believed that this tool can act positively in the control management, and improvement of fluid retention in the body in obese individuals. Objective: This study aims to present and compile the MB 3D Protocol for the treatment of obesity with the published evidence on Static Magnetic Fields (SMFs) applied in obesity. Materials and Methods: Qualitative and exploratory descriptive literature review. Results: Some studies were found that demonstrated that MB therapy can be beneficial for the treatment of obesity. The 3D Protocol has therapeutic potential to produce positive effects, being able to balance the body’s homeostasis by helping to regulate metabolism. Conclusion: Treatments with SMFs have beneficial effects on several aspects of obesity, which supports future studies that evaluate the results of applying the 3D Protocol in this area.